Binder solution, slurry, solid electrolyte layer, electrode and all-solid-state battery

By using an organic solvent with specific properties, the solubility and reactivity issues with vinylidene fluoride polymer are addressed, leading to improved ionic conductivity and performance in all-solid-state batteries.

JP7603789B2Active Publication Date: 2024-12-20KUREHA CORPORATION
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023500818
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-02-16
Filing Date
2022-02-14
Publication Date
2024-12-20
Estimated Expiration
2042-02-14

AI Technical Summary

Technical Problem

Existing solvents used in the production of all-solid-state battery electrodes, such as butyl butyrate and ethylene glycol monobutyl ether acetate, result in poor solubility and uniformity of vinylidene fluoride polymer, leading to decreased ionic conductivity due to reactivity with the solid electrolyte and formation of aggregates during slurry preparation.

Method used

Employing an organic solvent with a boiling point between 60°C and 160°C and a residual water content of 300 ppm or less, selected from cyclic ethers, ketones, and esters, to enhance the solubility and reduce reactivity of the vinylidene fluoride polymer, thereby improving the uniformity and conductivity of the solid electrolyte layer.

Benefits of technology

The proposed solvent system ensures high solubility and low reactivity, resulting in improved ionic conductivity of the solid electrolyte layer, enhancing the performance of all-solid-state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007603789000001
    Figure 0007603789000001
Patent Text Reader

Abstract

Provided are a binder solution, an electrode mixture, an electrode, and an all-solid battery that use an organic solvent for which reactivity with a solid electrolyte is low and solubility of a binder is high. An all-solid battery binder solution that includes an organic solvent and a binder that comprises a vinylidene fluoride polymer. The organic solvent is at least one selected from the group that consists of cyclic ethers, ketones, and esters, the boiling point of the organic solvent is 60°C–160°C, and the residual water content of the organic solvent is no more than 300 ppm.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a binder solution, a slurry, a solid electrolyte layer, an electrode, and an all-solid-state battery. [Background technology]

[0002] The electrodes of the all-solid-state battery are prepared, for example, by preparing a slurry by mixing a vinylidene fluoride polymer as a binder, an active material, a solid electrolyte, and a solvent, and then coating and drying the slurry on a current collector. If the solvent used in this case reacts with the solid electrolyte, the ionic conductivity of the solid electrolyte may decrease, and the battery performance may decrease. Therefore, the solvent must have low reactivity with the solid electrolyte, and as described in Patent Documents 1 and 2, butyl butyrate and the like have been used conventionally.

[0003] However, since vinylidene fluoride polymer has low solubility in solvents such as butyl butyrate, the slurry is a dispersion liquid in which vinylidene fluoride polymer is dispersed in a solvent, and the uniformity of vinylidene fluoride in the slurry is poorer than in a solution in which the polymer is dissolved in a solvent, and the active material and vinylidene fluoride may react to generate aggregates during the slurry preparation process. Therefore, a slurry using a solvent that has low reactivity with the solid electrolyte and high solubility of vinylidene fluoride is required.

[0004] As a technique using a solvent other than butyl butyrate, Patent Document 3 discloses a polymer solution intended for use in non-aqueous electrolyte secondary batteries, in which a vinylidene fluoride polymer is mixed with ethylene glycol monobutyl ether acetate. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2016-025025 A [Patent Document 2] JP 2016-025027 A [Patent Document 3] International Publication No. 2019 / 230140 Summary of the Invention [Problem to be solved by the invention]

[0006] However, according to the investigations of the present inventors, even when ethylene glycol monobutyl ether acetate is used as a solvent, the vinylidene fluoride polymer is not uniformly dissolved but is in a dispersed state, and it has been confirmed that when a slurry containing the solvent and a solid electrolyte is applied and dried to form a solid electrolyte layer, the ionic conductivity becomes very small.

[0007] The present invention has been made in view of the above problems, and has an object to provide a binder solution, a slurry, a solid electrolyte layer, an electrode, and an all-solid-state battery using an organic solvent that has low reactivity with a solid electrolyte and high binder solubility. [Means for solving the problem]

[0008] As a result of intensive research into solving the above-mentioned problems, the inventors have found that the above-mentioned problems can be solved by using a specific organic solvent having a boiling point in a specific range and a residual water content of not more than a specific amount, and have thus completed the present invention.

[0009] That is, the present invention provides a binder solution for an all-solid-state battery, comprising a binder made of vinylidene fluoride polymer and an organic solvent, The organic solvent is at least one selected from the group consisting of cyclic ethers, ketones, and esters; The boiling point of the organic solvent is 60° C. or more and 160° C. or less, The organic solvent has a residual water content of 300 ppm or less. This relates to a binder solution for an all-solid-state battery.

[0010] The boiling point of the organic solvent is preferably 80°C or higher and 160°C or lower.

[0011] The organic solvent is preferably at least one selected from the group consisting of 1,4-dioxane, ethyl butyrate, amyl acetate, isopropyl acetate, and ethyl propionate.

[0012] The vinylidene fluoride polymer is a copolymer containing a constituent unit derived from vinylidene fluoride and a constituent unit derived from hexafluoropropylene, The content of the structural units derived from the hexafluoropropylene is preferably 15% by mass or more based on the total structural units of the copolymer.

[0013] The present invention also relates to a slurry containing the binder solution and a solid electrolyte.

[0014] The present invention also relates to a solid electrolyte layer made from the slurry.

[0015] The ionic conductivity of the solid electrolyte layer is 0.05×10 -3 It is preferable that the viscosity is S / cm or more.

[0016] The present invention also relates to an electrode mixture containing the above slurry and an active material.

[0017] The present invention also relates to an electrode comprising the solid electrolyte layer.

[0018] The present invention also relates to an all-solid-state battery including the solid electrolyte layer. Effect of the Invention

[0019] According to the present invention, it is possible to provide a binder solution, a slurry, a solid electrolyte layer, an electrode, and an all-solid-state battery using an organic solvent that has low reactivity with a solid electrolyte and high binder solubility. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] [Binder solution for solid-state batteries] The binder solution for an all-solid-state battery of the present invention is a binder solution for an all-solid-state battery comprising a binder made of a vinylidene fluoride polymer and an organic solvent, The organic solvent is at least one selected from the group consisting of cyclic ethers, ketones, and esters; The boiling point of the organic solvent is 60° C. or more and 160° C. or less, The organic solvent has a residual water content of 300 ppm or less. Hereinafter, each component constituting the binder solution for an all-solid-state battery will be described.

[0021] (binder) In the present invention, a vinylidene fluoride polymer is used as the binder. The vinylidene fluoride polymer includes a homopolymer of vinylidene fluoride (VDF) and a copolymer of VDF and other monomers (hereinafter also referred to as "vinylidene fluoride copolymer"). The other monomer in the vinylidene fluoride copolymer is not particularly limited, and examples thereof include fluorine-based monomers copolymerizable with vinylidene fluoride or hydrocarbon-based monomers such as ethylene and propylene. Examples of fluorine-based monomers copolymerizable with vinylidene fluoride include vinyl fluoride, trifluoroethylene, tetrafluoroethylene, chlorotrifluoroethylene, hexafluoropropylene, and perfluoroalkyl vinyl ethers such as perfluoromethyl vinyl ether. Among these, hexafluoropropylene is preferred from the viewpoint of adhesion. The other monomers may be used alone, in combination of two types, or in combination of three or more types.

[0022] In the vinylidene fluoride copolymer, the content of structural units derived from other monomers is not particularly limited, but from the viewpoint of compatibility with the dispersion medium and solvent, for example, the content is preferably 15 mass% or more, more preferably 15 mass% or more and 40 mass% or less, and even more preferably 20 mass% or more and 35 mass% or less, based on the total structural units of the copolymer.

[0023] In the case where the vinylidene fluoride polymer is a copolymer containing a constituent unit derived from vinylidene fluoride and a constituent unit derived from hexafluoropropylene, or a copolymer consisting of only these two types of constituent units, the content of the constituent units derived from hexafluoropropylene is not particularly limited, but from the viewpoint of the adhesion of the electrode slurry, for example, it is preferably 15 mass% or more, more preferably 15 mass% or more and 40 mass% or less, and even more preferably 20 mass% or more and 35 mass% or less, of the total constituent units of the copolymer.

[0024] The molecular weight of the binder is not particularly limited, but is preferably from 200,000 to 1,500,000, and more preferably from 300,000 to 1,000,000.

[0025] The method for preparing the vinylidene fluoride polymer as the binder is not particularly limited, and is usually carried out by a method such as suspension polymerization, emulsion polymerization, solution polymerization, etc. From the viewpoint of ease of post-treatment, etc., aqueous suspension polymerization and emulsion polymerization are preferred, and from the viewpoint of particle dispersibility, emulsion polymerization which can give a polymer with a smaller particle size is more preferred.

[0026] A preparation example of the emulsion polymerization method will be described below. First, when preparing a vinylidene fluoride copolymer, vinylidene fluoride and other monomers, a liquid medium, and an emulsifier are mixed in an autoclave. The liquid medium is a liquid in which vinylidene fluoride and the like are poorly soluble. Then, a polymerization initiator soluble in the liquid medium is added to the mixed liquid to polymerize vinylidene fluoride, a fluorine-containing alkyl vinyl compound, and the like. When preparing a homopolymer of vinylidene fluoride, only vinylidene fluoride may be used as a monomer instead of vinylidene fluoride and other monomers in the above.

[0027] Here, it is preferable to maintain the pressure inside the autoclave during polymerization at approximately the same pressure for a certain period of time from the start of polymerization, and particularly from the start of polymerization (polymerization rate 0%) until the polymerization rate reaches 90% or more. As a method for maintaining the pressure at the start of polymerization, a method of adding a monomer immediately after adding an initiator can be mentioned. Moreover, the pressure inside the autoclave during polymerization is preferably 0 to 20 MPa, more preferably 0.5 to 15 MPa, and further preferably 1 to 10 MPa.

[0028] The liquid medium used in the emulsion polymerization is not particularly limited as long as it is a liquid in which the above-mentioned monomer is poorly soluble. The above-mentioned monomer is poorly soluble in water. Thus, an example of the liquid medium is water.

[0029] On the other hand, the emulsifier is not particularly limited as long as it can form micelles by monomers in a liquid medium and can stably disperse the synthesized polymer in the liquid medium, and for example, a known surfactant can be used. The emulsifier may be any of nonionic surfactants, cationic surfactants, anionic surfactants, and amphoteric surfactants, and these may be used in combination. Examples of emulsifiers include perfluorinated surfactants, partially fluorinated surfactants, and non-fluorinated surfactants that have been conventionally used in the polymerization of polyvinylidene fluoride. Among these surfactants, perfluoroalkylsulfonic acid and its salts, perfluoroalkylcarboxylic acid and its salts, and fluorosurfactants having a fluorocarbon chain or a fluoropolyether chain are preferred, and perfluoroalkylcarboxylic acid and its salts are more preferred. As the emulsifier, one or more types selected from the above can be used alone. The amount of emulsifier added is preferably 0.0001 to 22 parts by mass when the total amount of all monomers used in the polymerization is 100 parts by mass.

[0030] The polymerization initiator is not particularly limited as long as it is a compound that can dissolve in a liquid medium and polymerize a monomer. Examples of the polymerization initiator include known water-soluble peroxides, water-soluble azo compounds, and redox initiators. Examples of the water-soluble peroxides include ammonium persulfate and potassium persulfate. Examples of the water-soluble azo compounds include 2,2'-azobis-isobutyronitrile (AIBN) and 2,2'-azobis-2-methylbutyronitrile (AMBN). Examples of the redox initiators include ascorbic acid-hydrogen peroxide. Among these, water-soluble peroxides are preferred from the viewpoint of reactivity and the like. These polymerization initiators can be used alone or in combination of two or more. The amount of the polymerization initiator added is preferably 0.01 to 5 parts by mass, assuming that the total amount of all monomers used in the polymerization is 100 parts by mass.

[0031] The emulsion polymerization method may be a soap-free emulsion polymerization method, a mini-emulsion polymerization method, or a seed emulsion polymerization method.

[0032] The soap-free emulsion polymerization method is a method of emulsion polymerization without using the above-mentioned ordinary emulsifiers. The vinylidene fluoride copolymer obtained by the soap-free emulsion polymerization is preferable because the emulsifier does not remain in the polymer particles.

[0033] In addition, in the soap-free emulsion polymerization method, a reactive emulsifier having a polymerizable double bond in the molecule can also be used as the emulsifier. The reactive emulsifier forms micelles in the system at the beginning of the polymerization, but as the polymerization proceeds, it is used as a monomer in the polymerization reaction and consumed. Therefore, there is almost no free emulsifier in the final reaction system. Therefore, there is an advantage that the reactive emulsifier is less likely to bleed out onto the particle surface of the vinylidene fluoride copolymer obtained.

[0034] Examples of the reactive emulsifier include polyoxyalkylene alkenyl ether, sodium alkylaryl sulfosuccinate, sodium methacryloyloxypolyoxypropylene sulfate, and alkoxypolyethylene glycol methacrylate.

[0035] On the other hand, in the mini-emulsion polymerization method, a strong shearing force is applied using an ultrasonic oscillator or the like to reduce the size of monomer oil droplets to submicron size, and polymerization is then carried out. At this time, a known hydrophobe is added to the mixed liquid in order to stabilize the reduced size monomer oil droplets. In the mini-emulsion polymerization method, ideally, the polymerization reaction occurs only in each monomer oil droplet, and each oil droplet becomes a vinylidene fluoride polymer (fine particle). Therefore, it is easy to control the particle size and particle size distribution of the obtained vinylidene fluoride polymer.

[0036] Seed emulsion polymerization is a polymerization method in which the fine particles obtained by the above-mentioned polymerization method are coated with a polymer consisting of another monomer. A monomer, a liquid medium, a surfactant, a polymerization initiator, etc. are further added to the dispersion of the fine particles, and polymerization is carried out.

[0037] In any of the above emulsion polymerization methods, a chain transfer agent may be used to adjust the polymerization degree of the vinylidene fluoride polymer particles obtained. Examples of the chain transfer agent include ethyl acetate, methyl acetate, diethyl carbonate, acetone, ethanol, n-propanol, acetaldehyde, propylaldehyde, ethyl propionate, and carbon tetrachloride. If necessary, a pH adjuster may be used, which may include electrolyte substances having a buffering capacity, such as sodium dihydrogen phosphate, disodium hydrogen phosphate, and potassium dihydrogen phosphate, as well as basic substances, such as sodium hydroxide, potassium hydroxide, barium hydroxide, calcium hydroxide, and ammonia.

[0038] If necessary, other optional components such as anti-settling agents, dispersion stabilizers, corrosion inhibitors, anti-fungal agents, wetting agents, etc. The amount of these optional components added is preferably 0.005% to 10%, more preferably 0.01% to 7%, relative to the liquid medium.

[0039] In the polymerization of vinylidene fluoride polymer, the polymerization temperature may be appropriately selected depending on the type of polymerization initiator, etc., and may be set, for example, at 0 to 120° C., preferably 20 to 110° C., and more preferably 40 to 100° C. The polymerization time is not particularly limited, but is preferably 1 to 24 hours in consideration of productivity, etc.

[0040] (Organic solvent) The organic solvent is any one of a cyclic ether, a ketone, and an ester, and from the viewpoints of handling, safety, and drying properties of the slurry during production, the boiling point is 60°C or more and 160°C or less, preferably 90°C or more and 155°C or less, and more preferably 110°C or more and 150°C or less.

[0041] The organic solvent is preferably one with low hydrophilicity. If the organic solvent is highly hydrophilic, it is likely to adsorb moisture in the air. Even if a dehydration treatment is performed, the moisture contained in the organic solvent is difficult to remove, and a large amount of moisture may remain. The hydrophilicity of an organic solvent can be evaluated by the amount of water remaining in the organic solvent after a specific dehydration treatment. Specifically, 1 L of organic solvent and 100 g of molecular sieves are placed in a container with a lid, the container is sealed, and the organic solvent is stirred from time to time, and the amount of water remaining in the organic solvent after 24 hours is measured. The lower the amount of water remaining after the dehydration treatment, the lower the hydrophilicity is considered to be. If the water contained in the organic solvent reacts with the solid electrolyte, the solid electrolyte may deteriorate and the ionic conductivity may decrease. Therefore, the organic solvent is one in which the residual water content after dehydration treatment is 300 ppm or less, preferably 150 ppm or less, and more preferably 50 ppm or less. In addition, when the organic solvent contains a large amount of water, it is used after being dehydrated to reduce the residual water content to 300 ppm or less. The method for dehydrating the organic solvent is not particularly limited, but for example, a method of adding a molecular sieve, adding an alkali metal or benzophenone and distilling, or using a Grubbs column is preferable. From the viewpoint of preventing a decrease in the ionic conductivity of the solid electrolyte, the amount of water contained in the organic solvent is 300 ppm or less, preferably 150 ppm or less, and more preferably 50 ppm or less.

[0042] Examples of such organic solvents include dioxane, ethyl butyrate, amyl acetate, isopropyl acetate, ethyl propionate, and tetrahydrofuran.

[0043] (Other ingredients) The binder solution for an all-solid-state battery of the present invention may contain components other than the binder and the organic solvent (hereinafter, also referred to as "other components") as long as the effects of the present invention are not impaired. Examples of the other components include anti-settling agents, dispersion stabilizers, thickeners, and adhesive assistants.

[0044] (Method of making binder solution) The binder solution of the present invention can be prepared by mixing a binder, the specific organic solvent, and, if necessary, other components.

[0045] The binder solution of the present invention is a solution in which the specific binder used in the present invention is uniformly dissolved in a specific organic solvent, and the binder solution is transparent to the naked eye.

[0046] The content of the binder is not particularly limited, but is preferably 0.1% by mass or more, and more preferably 1% by mass or more, based on the total amount of the binder solution.

[0047] [slurry] The slurry of the present invention contains the above binder solution and a solid electrolyte. Further, the slurry (electrode binder) containing an active material includes a positive electrode slurry and a negative electrode slurry. In the positive electrode slurry, a positive electrode active material is used as the active material, and in the negative electrode binder slurry, a negative electrode active material is used as the active material. Hereinafter, each component constituting the slurry will be described.

[0048] (Positive electrode active material) As the positive electrode active material, a positive electrode active material known as a positive electrode active material of a solid battery can be used. For example, a lithium-based positive electrode active material containing lithium is preferable. Examples of the lithium-based positive electrode active material include, for example, LiCoO2, LiNi X Co 1-X Composite metal chalcogen compounds represented by the general formula LiMY2 (M is at least one of transition metals such as Co, Ni, Fe, Mn, Cr, and V; Y is a chalcogen element such as O and S) such as O2 (0 < x ≦ 1), composite metal oxides having a spinel structure such as LiMn2O4, and olivine-type lithium compounds such as LiFePO4. Note that commercially available products may be used as the positive electrode active material.

[0049] (Negative electrode active material) As the negative electrode active material, a negative electrode active material known as a negative electrode active material of a solid battery can be used. In particular, it is preferable to use a negative electrode active material capable of occluding and releasing lithium ions. For example, lithium alloys, metal oxides, carbon materials such as graphite and hard carbon, silicon and silicon alloys, Li4Ti5O 12 etc. are mentioned. In particular, graphite is preferable. The shape of the negative electrode active material is not particularly limited, but a powder form is preferable.

[0050] (Solid electrolyte) The solid electrolyte is not particularly limited as long as it is a solid compound having ion conductivity, and conventionally known inorganic solid electrolytes and polymer solid electrolytes can be used. Examples of the inorganic solid electrolyte include oxide-based solid electrolytes, sulfide-based solid electrolytes, nitride-based solid electrolytes, complex hydride solid electrolytes, etc. Further, examples of the polymer solid electrolyte include, for example , gel-based electrolytes, true polymer electrolytes, etc.

[0051] The oxide-based solid electrolyte is not particularly limited, but examples thereof include perovskite-type LLTO, garnet-type LLZ, NASICON-type compounds, LISICON-type compounds, LIPON-type compounds, and β-alumina-type compounds. Specific examples include Li3PO4, Li 0.34 La 0.51 TiO3, Li 1.3 Al 0.3 Ti 1.7 (PO4)3, Li7La3Zr2O 12 , Li6BaLa2Ta2O 12 , Li 2.9 PO 3.3 N 0.46 , Li 4.3 Al 0.3 S 0.7 O4, 50Li4SiO4-50Li3BO3, Li2O-Al2O3-SiO2-P2O5-TiO2, Li 1.5 Al 0.5 Ge 1.5 (PO4)3-0.05Li2O, etc.

[0052] The sulfide-based solid electrolyte is not particularly limited, but includes solid electrolytes containing Li, A (A is at least one of P, Si, Ge, Al, and B), and S, and the sulfide-based solid electrolyte may further contain a halogen element. In addition, LGPS-type compounds, argyrodite-type compounds, amorphous compounds, Li-PS-type compounds, etc. are also included. Specific examples include Li2S-P2S5, Li2S-P2S3, Li2S-P2S3-P2S5, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, LiI-Li2S-SiS2-P2S5, Li2S-SiS2-Li4SiO4, Li2S-SiS2-Li3PO4, Li3PS4-Li4GeS4, Li 3.4 P 0.6 S 0.4 S4, Li 3.25 P 0.25 Ge0.76 S4, Li 3.25 P 0.75 Ge 0.25 S4, Li 10 GeP2S 12 , Li 4-x Ge 1-x P x S4, Li6PS5Cl, Li6PS5Br, Li6PS5I, etc.

[0053] The nitride-based solid electrolyte is not particularly limited, but a specific example is LiN3.

[0054] The complex hydride solid electrolyte is not particularly limited, but a specific example is LiBH4.

[0055] The gel electrolyte is not particularly limited, but specific examples include Poly(ethylene oxide)8-LiClO4 (ethylene carbonate (EC) + propylene carbonate (PC)), Poly(ethylene oxide)8-LiClO4 (PC), Poly(vinylidene fluoride)-LiN(CF3SO2)2 (EC + PC), Poly(vinylidene fluoride-co-hexafluoropropylene)-LiPF6 (EC + diethyl carbonate (DEC) + dimethyl carbonate (DMC)), Poly(ethylene glycol acrylate)-LiClO4 (PC), Poly(acrylonitrile)-LiClO4 (EC + PC), Poly(methyl methacrylate)-LiClO4 (PC), and the like.

[0056] The intrinsic polymer electrolyte is not particularly limited, but specific examples include Poly(ethylene oxide)8-LiClO4, Poly(oxymethylene)-LiClO4, Poly(propylene oxide)8-LiClO4, Poly(dimethyl siloxane)-LiClO4, Poly(vinylidene fluoride-co-hexafluoropropylene)-LiTFSI, Poly(2,2-dimethoxypropylene carbonate)-LiFSI, Poly[(2-methoxy)ethylglycidyl ether]8-LiClO4, and the like.

[0057] The solid electrolyte may contain only one of the above electrolytes, or may contain two or more of them.

[0058] (Other ingredients) The slurry of the present invention may contain components other than the binder solution, the active material, and the solid electrolyte (hereinafter, also referred to as "other components"), so long as the effects of the present invention are not impaired. Examples of the other components include a conductive assistant, a thickener, a sedimentation inhibitor, a dispersion stabilizer, and an adhesion assistant.

[0059] (Slurry manufacturing method) The slurry of the present invention can be prepared by mixing the binder solution, the solid electrolyte, and, if necessary, an active material and other components. The content of each of the above components may be any content that allows the solid electrolyte layer to function properly, and any known content may be used.

[0060] [Solid electrolyte layer] The solid electrolyte layer of the present invention can be obtained by applying the above-mentioned slurry to the surface of a current collector or an electrode and drying it. The application method is not particularly limited, and for example, a doctor blade method, a reverse roll method, a comma bar method, a gravure method, an air knife method, a die coating method, a dip coating method, etc. can be applied. After the application of the slurry, it is common to heat it at an arbitrary temperature to dry the solvent. Drying may be performed multiple times at different temperatures. Pressure may be applied during drying. After drying, a heat treatment may be further performed. In one example, the heat treatment is performed at 50°C or higher and 300°C or lower for 10 seconds to 300 minutes. The ionic conductivity of the obtained solid electrolyte layer is not particularly limited, but is preferably 0.05×10 -3 The viscosity is preferably 0.02 S / cm or more, more preferably 0.07 S / cm or more, and even more preferably 0.09 S / cm or more.

[0061] [electrode] In one embodiment, the electrode of the present invention includes the solid electrolyte. More specifically, the electrode of the present invention has a current collector and a solid electrolyte layer (electrode mixture layer) formed on a surface of the current collector. As described above, the electrode mixture layer is obtained by applying the slurry (electrode mixture) of the present invention containing an active material onto the current collector and drying it.

[0062] The current collector is not particularly limited, and may be a metal foil or metal steel such as aluminum, copper, iron, stainless steel, steel, nickel, titanium, etc. Alternatively, the current collector may be a medium having the above-mentioned metal foil or metal steel applied to the surface thereof.

[0063] After the coating and drying, a press treatment may be further performed. In one example, the press treatment is performed at a pressure of 1 kPa or more and 10 GPa or less. By performing the press treatment, the electrode density can be improved.

[0064] [All-solid battery] The all-solid-state battery of the present invention includes the above-mentioned solid electrolyte layer. More specifically, the all-solid-state battery of the present invention may be one in which a positive electrode, a solid electrolyte layer, and a negative electrode are laminated, or an electrode having a solid electrolyte layer (electrode mixture layer) on either the positive electrode or the negative electrode as described above may be used. When using an electrode that is not produced by the method of the present invention, a known electrode can be used, and a known solid electrolyte can be used for the solid electrolyte layer. EXAMPLES

[0065] The present invention will be described in more detail below based on examples and comparative examples, but the present invention is not limited to the following examples.

[0066] [Example of binder preparation] 280 parts by mass of ion-exchanged water was put into the autoclave, and degassed by bubbling with nitrogen for 30 minutes. Next, 0.2 parts by mass of disodium hydrogen phosphate and 0.003 parts by mass of polyoxyethylene alkylene alkyl ether were charged, and the pressure was increased to 4.5 MPa, and nitrogen substitution was performed three times. Then, 0.1 parts by mass of ethyl acetate, 8 parts by mass of vinylidene fluoride (VDF), and 27 parts by mass of hexafluoropropylene (HFP) were added to the autoclave. The temperature was raised to 80°C while stirring. Then, a 5% by mass aqueous solution of ammonium persulfate (APS) was added so that the amount of APS was 0.06 parts by mass, and polymerization was started. The pressure inside the autoclave at this time was 2.5 MPa. 65 parts by mass of VDF were continuously added immediately after the start of polymerization so that the pressure inside the autoclave was maintained at 2.5 MPa at the start of polymerization. After the addition was completed, the polymerization was completed when the pressure dropped to 1.5 MPa, and a latex (resin composition) was obtained. The solid concentration of the obtained latex (concentration of vinylidene fluoride copolymer) was 21.0% by mass. Then, only the vinylidene fluoride copolymer was extracted from the latex by salting out to obtain a binder (VDF / HFP) made of the vinylidene fluoride copolymer with VDF:HFP=73% by mass:27% by mass.

[0067] <Preparation of binder liquid> [Examples 1 to 6, Comparative Examples 1 to 3] (binder) In Examples 1 to 6 and Comparative Examples 1 to 3, the vinylidene fluoride copolymer VDF / HFP prepared above was used as the binder.

[0068] (Organic solvent) In Examples 1 to 6 and Comparative Examples 1 to 3, the following organic solvents were used after being subjected to a dehydration treatment described below. (Type of organic solvent) Dioxane (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) Ethyl butyrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) Amyl acetate (Tokyo Chemical Industry Co., Ltd.) Isopropyl acetate (Tokyo Chemical Industry Co., Ltd.) Ethyl propionate (Tokyo Chemical Industry Co., Ltd.) Tetrahydrofuran (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) Ethylene glycol monobutyl ether acetate (Tokyo Chemical Industry Co., Ltd.) Butyl butyrate (Kishida Chemical Co., Ltd.) Morpholine (Tokyo Chemical Industry Co., Ltd.)

[0069] (Dehydration of organic solvents) For dioxane and tetrahydrofuran, ultra-dehydrated solvents (water content 10 ppm or less) were used. For other organic solvents, 1 L of organic solvent and 100 g of molecular sieve 3A were placed in a container with a lid and sealed to remove the water. The mixture was stirred continuously, and the residual water content of the organic solvent was measured after 24 hours. The molecular sieves used were dried overnight at 300°C under reduced pressure. The residual water content was measured using a trace water content measuring device (Mitsubishi Chemical Corporation, CA-100 model) by applying the principle of the Karl Fischer reaction to the coulometric titration method. The resulting residual water content is shown in Table 1.

[0070] (Preparation of binder liquid) Five parts by mass of the powdered binder and 95 parts by mass of the organic solvent after the dehydration treatment were mixed and stirred while being heated in an oil bath at 70° C. to prepare a binder liquid.

[0071] <Evaluation> [Solubility of binder] The obtained binder liquid was allowed to stand, and the state of dissolution of the binder was visually observed and evaluated according to the following criteria. The results are shown in Table 1. ◯: The binder liquid is uniform and transparent. ×: Turbidity or sedimentation was observed in the binder liquid.

[0072] <Creating a solid electrolyte layer model> [Examples of preparation of solid electrolyte layer model using organic solvent examined in Examples 1 to 6 and Comparative Examples 1 to 3] The solid electrolyte layer is prepared by removing the organic solvent from a slurry containing a binder solution and a solid electrolyte. In this experiment, in order to directly examine the reactivity of the organic solvent with the solid electrolyte, a solid electrolyte layer model containing no binder was prepared and the ionic conductivity of the solid electrolyte layer model was measured.

[0073] 200 mg of Li6SP5Br, which is a type of sulfide-based solid electrolyte, and 2 mL of the organic solvent used in preparing the binder solution in Examples 1 to 6 and Comparative Examples 1 to 3 were mixed, and the resulting mixture was left to stand for 1 hour, and then dried under reduced pressure at 90°C for 2 hours to remove the organic solvent. In addition, for the mixture obtained using ethylene glycol monobutyl ether acetate as the organic solvent, the supernatant was removed by decantation after leaving it to stand for 1 hour, and the organic solvent was removed by drying under reduced pressure at 120°C for 2 hours. 150 mg of the sulfide-based solid electrolyte from which the organic solvent had been removed was placed in a 10 mmΦ ceramic cylindrical cell, pressurized at 500 MPa, and then the cylindrical cell was fixed with a bolt at 8 N, and pressed into pellets to prepare a solid electrolyte layer model.

[0074] <Evaluation> [Ionic conductivity] The impedance of the obtained solid electrolyte layer model was measured using VersaSTAT4 manufactured by Princeton Applied Research. AC impedance measurement was performed at a frequency of 1 MHz to 0.1 Hz and a temperature of 25° C., and ionic conductivity was calculated based on the measurement results. The results are shown in Table 1 as "ionic conductivity" for Examples 1 to 6 and Comparative Examples 1 to 3.

[0075] [Table 1]

[0076] From Table 1, in Comparative Example 2 in which butyl butyrate was used as the organic solvent, the ion conductivity of the solid electrolyte layer model was high, but the binder did not dissolve. In addition, when ethylene glycol monobutyl ether acetate was used as the organic solvent, the binder did not dissolve and the ion conductivity of the solid electrolyte layer model was also low, as shown in Comparative Example 1. In Comparative Example 3 in which morpholine was used as the organic solvent, the binder dissolved, but the ion conductivity of the solid electrolyte layer model decreased and was below the measurement limit (unmeasurable) because morpholine has high hydrophilicity and there was a lot of residual moisture after dehydration treatment. On the other hand, when an organic solvent that is any of cyclic ethers, ketones, and esters and has a boiling point of 60°C to 160°C was used, it was found that the binder dissolved in each solvent and the ion conductivity of the solid electrolyte layer model was also high, as shown in Examples 1 to 6.

Claims

1. A slurry containing a binder solution for an all-solid-state battery, the binder solution containing a binder made of a vinylidene fluoride polymer and an organic solvent, and a sulfide-based solid electrolyte, the organic solvent is at least one selected from the group consisting of a cyclic ether, a ketone, and an ester, the boiling point of the organic solvent is 60° C. or higher and 160° C. or lower, and the residual water content of the organic solvent is 300 ppm or less, The vinylidene fluoride polymer is a copolymer containing a constituent unit derived from vinylidene fluoride and a constituent unit derived from hexafluoropropylene, The content of the structural units derived from the hexafluoropropylene is 15% by mass or more and 35% by mass or less, based on all structural units of the copolymer, and the content of the structural units derived from the vinylidene fluoride is 65% by mass or more and 85% by mass or less, based on all structural units of the copolymer.

2. The slurry according to claim 1 , wherein the boiling point of the organic solvent is 80° C. or more and 160° C. or less.

3. The slurry according to claim 1 or 2, wherein the organic solvent is at least one selected from the group consisting of 1,4-dioxane, ethyl butyrate, amyl acetate, isopropyl acetate, and ethyl propionate.

4. A solid electrolyte layer produced from the slurry according to any one of claims 1 to 3, having an ionic conductivity of 0.05 × 10 -3 A solid electrolyte layer having a specific resistance of 100 S / cm or more.

5. An electrode mixture comprising the slurry according to any one of claims 1 to 3 and an active material.

6. An electrode comprising the solid electrolyte layer of claim 4.

7. An all-solid-state battery comprising the solid electrolyte layer according to claim 4.

Citation Information

Patent Citations

  • Lithium ion secondary battery

    JP2000082470A

  • Electrode for lithium secondary battery and manufacturing method thereof, and lithium secondary battery including the same electrode

    JP2010262916A

  • Method for manufacturing negative electrode for solid battery, method for manufacturing solid battery, and slurry for negative electrode

    JP2016025025A

  • Method for manufacturing positive electrode for solid battery, method for manufacturing solid battery, and slurry for positive electrode

    JP2016025027A

  • All-solid type secondary battery, composition for electrode active material layer, electrode sheet for all-solid type secondary battery, and manufacturing methods for all-solid type secondary battery and electrode sheet for all-solid type secondary battery

    JP2016212990A